MODIFICATION OF SIZE EFFECT FORMULA FOR CONCRETE BEAMS WITHOUT SHEAR REINFORCEMENT - Kerelezova, Irina (Journal of Applied Engineering Science, 2026)
The current state of engineering science and practice has been concluded that the size effect cannot be overlooked, especially in the calculation of the shear capacity. Models based entirely on fracture mechanics have led to complex formulations inconvenient for practical use. Models based on simple theories, are resulting in a formula for determining the shear capacity of reinforced concrete. They are practically convenient, but multiple empirical parameters without a clear physical meaning are involved in their formulation. In the present study one modification of a size effect formula is presented. The purpose of this modification is to replace an empirical coefficient with a fracture mechanic’s parameter with a clear physical meaning.